The association of cemiplimab plus sonidegib for synchronous cutaneous squamous cell carcinoma and basal cell carcinoma of the head and neck: Two case reports - Colombo, Elena; Gurizzan, Cristina; Ottini, Arianna; Caspani, Francesca; Bergamini, Cristiana; Locati, Laura D.; Marchiselli, Chiara; Alberti, Andrea; Lorini, Luigi; Licitra, Lisa F.; Bossi, Paolo; Resteghini, Carlo (Frontiers in Oncology, 2023)
Basal cell carcinoma (BCC) and cutaneous squamous cell carcinoma (cSCC) are the most frequent cancers in humans, with cumulative ultraviolet radiation exposure, aging and immunodepression as the main risk factors. In most cases, these malignancies arise in the area of head and neck, and they can be treated with locoregional therapies. A minority of cases requires systemic therapy. Currently, sonic hedgehog inhibitors (i.e. vismodegib, sonidegib) are approved for advanced BCC, while the PD-1 checkpoint inhibitor cemiplimab is approved in first line for cSCC, and in second line for BCC. Nevertheless, there is a clinical need for an effective and safe treatment for advanced synchronous (syn) BCC/cSCC not amenable to local treatments. International guidelines do not provide specific recommendations for patients affected by this condition, and no case reports on the full-dose association of these medications have been previously reported. Here we present the cases of two elderly patients affected by synBCC/cSCC of the head and neck, who received combined therapy with cemiplimab and sonidegib at full dose and standard schedule, achieving remarkable clinical benefit and long-term responses, without major adverse events. The instance of a feasible treatment for patients with advanced synBCC/cSCC will become increasingly frequent with the advancement of life expectancy in the global population, and the synergistic activity of targeted therapies and immunotherapy – administered either in association or sequentially – deserves to be further explored.